2017
DOI: 10.1111/nhs.12356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of near‐infrared rays on female menstrual pain in Korea

Abstract: Most Korean women who experience menstrual pain have reported taking pain medicine and making use of complementary alternative therapies. However, because some interventions may cause side effects, more effective pain-relieving measures need to be identified. This study using a non-equivalent group design, evaluated the effects of near-infrared rays on dysmenorrhea among Korean women. The experimental group wore a near-infrared ray abdominal belt for the duration of one menstrual cycle until the end of the men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Second, the moxibustion instrument has infrared treatment function. Although this study did not explore the role of infrared in the treatment of pelvic floor myofascial pain, a number of studies have shown [ 8 , 31 , 32 ] that infrared radiation is conducive to reducing pain. Consistently, we found that moxibustion at the trigger points of the governor vessel meridian and pelvic myofascial was more effective than Celebrex treatment and lifestyle change in patients with pelvic floor myofascial pain syndrome ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the moxibustion instrument has infrared treatment function. Although this study did not explore the role of infrared in the treatment of pelvic floor myofascial pain, a number of studies have shown [ 8 , 31 , 32 ] that infrared radiation is conducive to reducing pain. Consistently, we found that moxibustion at the trigger points of the governor vessel meridian and pelvic myofascial was more effective than Celebrex treatment and lifestyle change in patients with pelvic floor myofascial pain syndrome ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Authors have suggested that the warmth produced by these tools improves abdominal blood supply and their efficacy can be safely compared to the use of oral analgesics. 61…”
Section: Less-explored Approaches On the Management Of Pdmentioning
confidence: 99%
“…A recent study on 218 Korean adolescent girls is the only such study to demonstrate that concern for the environment and self-appraisal of exposure to endocrine disruptors were significant factors explaining health behaviors [17]. In addition, women who experienced menstrual pain [18] and environmental illnesses such as allergies and asthma [19] were found to practice avoidance behaviors toward endocrine disruptors. This limited evidence warrants further investigation of the responses and actions of women toward environmental hazards.…”
Section: Introductionmentioning
confidence: 99%